New NSIC-Approved varieties of snap beans (Phaseolus vulgaris) in Benguet, Philippines. (The Philippine Journal of Crop Science, 2010)
The snapbean breeding program jointly undertaken by the Benguet-State University and the Institute of Plant Breeding, University of the Philippines Los Banos at the University of the Philippines Los Banos at the BSU-IPB Highland Crops Research Station (HCRS) resulted to selection and identification of nine pole snap bean and seven bush snap bean promising improved varieties with higher yield and better agronomic characteristics than the traditional commercial varieties. They were further evaluated in multi-location field trials from 2005-2009 that led to official approval and registration of three new improved varieties of pole snap beans and two new improved varieties of bush snap bean for regional commercialization by the DA-NSIC in November 2008 and 2009. They were NSIC 2008 PSnBn 1”Kapangan”, NSIC 2008 PSnBn 2 “Mabunga” and NSIC 2009 PSnBn 1 “Tublay” pole snap bean varieties and NSIC 2009 BSnBn 1 “Sablan” and NSIC 2009 BSnBn 2 “Bokod” bush snap bean varieties.